Acceptability and Nutritional Content of Morijell Instant Pudding as an Additional Food for Nutritionally Vulnerable Groups - Fauziah, Fauziah; Hendrayati, Hendrayati; Kartini B, Thresia Dewi; Khaerawati, ST. (Jurnal Ilmiah Kesehatan (JIKA), 2024)
One of the causes of nutritional problems, especially in vulnerable groups such as pregnant-women and toddlers, is due to a lack of energy and nutritional intake. Utilization of Morijell (instant pudding from Moringa-leaves) as an alternative additional food as an effort to improve the nutritional status of toddlers and pregnant women. This study aimed to assess the acceptability and nutritional content of Morijell. It was an experimental research based on completely randomized design. The research results were analyzed using the Kruskal Wallis test to test differences in acceptability and the T-test was used to compare selected formula nutrients with controls. The acceptability assessment results showed that Morijell instant pudding was acceptable with the best formula score=6,024. The most popular instant-pudding formula enriched with Moringa leaf powder is Morijell with the addition of 4 g Moringa leaf powder (F1). Significant differences in the Morijell instant pudding hedonic test were seen in the aroma and taste attributes (p-value<0,05), while the texture and color attributes didn’t significantly influence panelist acceptance (p-value>0,05). The results of the nutritional analysis of the best formula show significant differences in protein, fat and calcium (p-value<0,05). The best formula contains energy=197,56 kcal, protein=6,65 grams, fat=6,28 grams, iron=3,82 mg and calcium=336,17 mg. In conclusion, the addition of Moringa-leaf-powder affects the aroma and taste but doesn’t affect the color and the texture.